AI-Powered Carotid Stenosis Detection Using Ultrasound Doppler Analysis - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Explore AI-driven ultrasound Doppler analysis for automatic carotid stenosis detection and quantification, improving diagnosis accuracy and clinical decision-making.
Keywords: AI; Carotid Stenosis; Ultrasound Doppler; Medical Imaging; Digital Health